Pengaruh Daya Tarik Iklan Dan Online Customer Review Terhadap Minat Beli Pada Masyarakat Pengguna Aplikasi Shopee Di Kecamatan Percut Sei Tuan - Wira Hayati Putri; Wan Suryani (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
The purpose of this study was to determine and analyze The Effect Of The Attractiveness Of Advertising And Online Customer Review On Buying Interest In The Society User The Shopee Application In Percut Sei Tuan District. The research model used is associative research, where the variables are measured using a likert scale. The data collection method is carried out using a questionnare with a list of questions or questionnaires that have been prepared in advance and given to respondents. The population in this study is The Society User The Shopee Application In Percut Sei Tuan District, Tembung, Deli Serdang that totaling 402.468 respondents. Because of large population, the authors took 1 urban village namely Tembung Urban Village, which amoundted to 56.104 respondents. The sampling method using the slovin method in this study, the sample obtained was 100 respondents. Data processing using SPSS Version 22 software, with descriptive analysis and multiple regression analysis and multiple reggression analysis hypothesis testing. The results of the study show that (1) Partially The Attractiveness Of Advertising affects Buying Interest (2) Partially Online Customer Review affects Buying Interest (3) Simultaneously there is a positive and significant influence between The Attractiveness Of Advertising And Online Customer Review On Buying Interest In The Society User The Shopee Application In Percut Sei Tuan District.